Toxicity of dietary Heliotropium dolosum seed to broiler chickens - Eröküz, Y; Eröksüz, H; Özer, H; Canatan, H; Yaman, I; Çevik, A (Comparative Toxicology Lab, 2001)
Five groups of 20 female broiler chicks were fed different levels of dehulled Heliotropium dolosum seed (w/w %; 0.0, 1.0. 3.0, 5.0 or 10.0%) from 10 to 52 d of age. In all doses the seed caused decreases in claim feed intake, weight gain, and feed efficiency, and biochemical findings, severity of pathologic changes, and mortality rate increased in a dose-dependent manner. Acute toxicity was observed in livers of chicks fed 10% seed. Other test groups had chronic changes. Livers had massive to submassive necrosis, hepatic megalocytosis, bile duct proliferation, fatty change, and periportal fibrosis, Biochemical evaluations revealed hypoalbuminemia, hypoprotienemia and increased ALP activity and billuribin. The seed of Heliotropium dolosum produced biochemical and specific pathologic changes in broiler chicks, as well as decreased food intake and feed efficiency. Higher seed levels induced more pronounced changes.
Keywords: Pyrrolizidine Alkaloids; Senecio-Jacobaea; Ragwort; Liver